Leukadherin-1-Mediated Activation of CD11b Inhibits LPS-Induced Pro-inflammatory Response in Macrophages and Protects Mice Against Endotoxic Shock by Blocking LPS-TLR4 Interaction - Yao, Xiaoying; Dong, Guanjun; Zhu, Yuzhen; Yan, Fenglian; Zhang, Hui; Ma, Qun; Fu, Xingqin; Li, Xuehui; Zhang, QingQing; Zhang, Junfeng; Shi, Hui; Ning, Zhaochen; et al. (Frontiers in Immunology, 2019)
ABSTRACT Dysregulation of macrophage has been demonstrated to contribute to aberrant immune responses and inflammatory diseases. CD11b, expressed on macrophages, plays a critical role in regulating pathogen recognition, phagocytosis, and cell survival. In the present study, we explored the effect of leukadherin-1 (LA1), an agonist of CD11b, on regulating LPS-induced pro-inflammatory response in macrophages and endotoxic shock. Intriguingly, we found that LA1 could significantly reduce mortalities of mice and alleviated pathological injury of liver and lung in endotoxic shock. In vivo studies showed that LA1-induced activation of CD11b significantly inhibited the LPS-induced pro-inflammatory response in macrophages of mice. Moreover, LA1-induced activation of CD11b significantly inhibited LPS/IFN-γ-induced pro-inflammatory response in macrophages by inhibiting MAPKs and NF-κB signaling pathways in vitro. Furthermore, the mice injected with LA1-treated BMDMs showed fewer pathological lesions than those injected with vehicle-treated BMDMs in endotoxic shock. In addition, we found that activation of TLR4 by LPS could endocytose CD11b and activation of CD11b by LA1 could endocytose TLR4 in vitro and in vivo, subsequently blocking the binding of LPS with TLR4. Based on these findings, we concluded that LA1-induced activation of CD11b negatively regulates LPS-induced pro-inflammatory response in macrophages and subsequently protects mice from endotoxin shock by partially blocking LPS-TLR4 interaction. Our study provides a new insight into the role of CD11b in the pathogenesis of inflammatory diseases.